Xiquexique (Pilosocereus gounellei (A. Weber ex K. Schum.) Bly. ex Rowl.) em substituição à silagem de sorgo (Sorghum bicolor L. Moench) na alimentação de vacas leiteiras Replacement of sorghum silage (Sorghum bicolor L. Moench) with a columnar cactus (Pilosocereus gounellei (A. Weber ex K. Schum.) Byl ex Rowl.) on diets of lactating dairy cows - José Geraldo Medeiros da Silva; Divan Soares da Silva; Marcelo de Andrade Ferreira; Guilherme Ferreira da Costa Lima; Airon Aparecido Silva de Melo; Marcus César Nóbrega Montenegro Diniz (Revista Brasileira de Zootecnia, 2005)
O desempenho de vacas da raça Pardo-suíça em lactação e a digestibilidade aparente de dietas contendo níveis de 0; 12,5; 25; 37,5 e 50% de xiquexique (Pilosocereus gounellei (A. Weber ex K. Schum.) Bly. ex Rowl.) em substituição à silagem de sorgo (Sorghum bicolor L. Moench) foram avaliados utilizando-se cinco vacas com peso vivo (PV) médio de 520 kg e produção média diária de 15 kg de leite. O delineamento experimental foi em quadrado latino (5x5) e constou de cinco animais, cinco períodos e cinco níveis de inclusão de xiquexique na dieta. Cada período experimental teve duração de 17 dias ( dez destinados à adaptação dos animais às dietas e sete para coleta). Os consumos de matéria seca (MS), em kg/dia, % e em unidade de tamanho metabólico (g/kg0,75), de matéria orgânica (MO), de proteína bruta (PB) e de carboidratos totais (CHT), em kg/dia, não foram influenciados pela inclusão de xiquexique na dieta, apresentando valores médios de 15,21; 2,83; 136,10; 13,64; 1,64 e 11,48 kg respectivamente. Os consumos de fibra em detergente neutro (FDN), extrato etéreo (EE) e nutrientes digestíveis totais (NDT), em kg/dia, diminuíram, enquanto o de carboidratos não-fibrosos (CNF), em kg/dia, elevou linearmente com a inclusão de xiquexique na dieta. A inclusão de xiquexique na dieta não influenciou as digestibilidades de matéria seca (DAMS), matéria orgânica (DAMO), proteína bruta (DAPB), extrato etéreo (DAEE), fibra em detergente neutro (DAFDN) e dos carboidratos totais (DACHT). Não houve efeito da inclusão de xiquexique na dieta sobre a produção (média de 14,80 kg/dia) e na composição química do leite e a eficiência alimentar (kg de leite produzido/kg de MS consumida). Five lactating Brown-Swiss cows averaging 520 kg of body weight (BW) and 15 kg of milk yield were assigned to a 5 x 5 Latin square to study the effects of replacing sorghum silage (Sorghum bicolor L. Moench) with a columnar cactus known as xiquexique (Pilosocereus gounellei (A. Weber ex K. Schum.) Byl ex Rowl.) on animal performance and apparent digestibility of nutrients. The experimental diets contained (DM basis): 0, 12.5, 25, 37.5, or 50% of xiquexique. Each experimental period lasted 17 days (10 days for diet adaptation and 7 days for sample collection). Intake of dry matter (DM) expressed as amount (kg/d), as percentage of BW, or as metabolic weight (g/kg0.75) were 15.21 kg/d, 2.83% of BW, and 136.10 g/kg0.75 and did not change by replacing sorghum silage with xiquexique in the diet. Similarly, intake of organic matter (OM), crude protein (CP), and total carbohydrates (TCH) did not differ and averaged 13.64, 1,64, and 11,48 kg/d across diets, respectively. However, intake (kg/d) of neutral detergent fiber (NDF), ether extract (EE), and total digestible nutrients (TDN) all decreased linearly (P < 0.01) while the opposite was observed for non-fiber carbohydrates (NFC) by replacing sorghum silage with xiquexique in the diet. No significant differences in the apparent digestibility of DM (DMAD), organic matter (OMAD), crude protein (CPAD), ether extract (EEAD), neutral detergent fiber (NDFAD), and total carbohydrates (TCHAD) were observed by increasing the dietary proportions of xiquexique. Milk yield averaged 14.80 kg/d and also did not differ among treatments in the present trial. Following the same trend, milk composition and feed efficiency (kg of milk yield/kg of DM intake) were unaffected by increasing the levels of xiquexique in the diet.